2001
DOI: 10.1038/sj.ijo.0801806
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen deficiency causes central leptin insensitivity and increased hypothalamic neuropeptide Y

Abstract: OBJECTIVE: Altered fat distribution is a consequence of menopause, but the mechanisms responsible are unknown. Estrogen insufficiency in humans can be modeled using ovariectomized rats. We have shown that increased adiposity in these rats is due to reduced physical activity and transient hyperphagia, and can be reversed with 17b-estradiol treatment. The aims of this study were to examine whether this altered energy balance is associated with circulating leptin insufficiency, central leptin insensitivity, decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
102
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(116 citation statements)
references
References 54 publications
11
102
2
1
Order By: Relevance
“…Studies in humans (16) and rodents (8,9) have established a potential role for elevated NPY in the accumulation of WAT that occurs with menopause. Our findings are supportive of a role for the NPY system in the regulation of WAT content following the removal of gonadal hormones and strongly suggest a role for Y2 receptors in the control of this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in humans (16) and rodents (8,9) have established a potential role for elevated NPY in the accumulation of WAT that occurs with menopause. Our findings are supportive of a role for the NPY system in the regulation of WAT content following the removal of gonadal hormones and strongly suggest a role for Y2 receptors in the control of this process.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in body fat mass following menopause contributes to an increased risk of cardiovascular and metabolic diseases (6,7). This increase in adipose tissue is associated with a corresponding increase in levels of the Y2 receptor ligand neuropeptide Y (NPY) 3 (8,9). Thus Y2 receptors may play an important role in two of the major endocrine consequences of sex hormone deficiency, bone loss and adipose accumulation.…”
mentioning
confidence: 99%
“…Data from several animal experiments clearly show that oestrogen deficiency in ovx rats may increase food intake (Gray and Wade, 1981;Pedersen et al, 2001) and decrease adipose tissue lipolysis (Darimont et al, 1997), spontaneous physical activity (Roy and Wade, 1975), and energy expenditure (Heine et al, 2000;Pedersen et al, 2001). Also, it has been shown that hypoestrogenemia in ovx rats causes central leptin insensitivity and increases hypothalamic neuropeptide Y levels and thereby contribute to excess fat accumulation (Ainslie et al, 2001). Results from human studies have also demonstrated that women who became postmenopausal had significantly greater reductions in resting metabolic rate and lower physical activity levels compared to their premenopausal controls (Ravussin et al, 1988;Poehlman et al, 1995).…”
Section: Menopause Hormonal Changes and Obesitymentioning
confidence: 99%
“…Indeed, selective deletion of AR in mature osteoblasts decreases bone mass [6] and reduces bone formation [7], whereas chronic subcutaneous testosterone treatment in rats stimulates bone formation [5, androgens on bone mass and bone form with the fact that low serum testoster factor for fracture in men, nearly dou fracture in men over 60 years of age androgens also seem to be importan mass in women, because women wit tivity syndrome have lower bone min estrogen and progesterone treatment androgens influence bone mass in me women, and this can occur via direct e particularly osteoblasts. This is in keep that failure of osteoblastic function i nopausal period in females, as well a crucial for the development of osteopo In addition to effects on bone homeo have pronounced effects on adipose ti gen deficiency in female animals is as phagia and increased body weig particularly visceral adiposity [2,3,35, studies (although not all) report that m ated with weight gain, even after contr of age [37,38]. Discrepancies among probably due to the fact that body we large epidemiological studies -is not body composition, and more accurat composition and fat distribution wou sistent findings.…”
mentioning
confidence: 99%